Pengaruh kopi Aceh ulee kareng terhadap kekerasan basis gigitiruan resin akrilik Effect of ulee kareng Aceh coffee the hardness of acrylic resin denture base - Rini Defika Putri; Viona Diansari; Iin Sundari (DiscoverSys Inc., 2011)
The hardness of denture base is influenced with the habit of most commonly consumed. Ulee Kareng Aceh coffeewas atype of robusta coffee which is acidic. The purpose of this study was to determine the change of surfacehardness of acrylic denture base after being immersed in ulee kareng coffee for 3 days. Twelve specimens (5 mmdiameter and 2 mm thickness)were randomly distributed in two groups: control (immersion in distilled water) andexperimental (immersion in Ulee Kareng Aceh coffee). Hardness was measured before and after immersion usingKnoop Microhardness tester (Shimadzu). Data were statistically analyzed by Mann Whitney and Wilcoxon test (Î± =0.05). The results of the study showed a significant difference between the groups P < 0.05. The surface hardness ofacrylic denture base decreased after immersion for both group P < 0.05.